The Pseudo-Xenophon’s Constitution of the Athenians (Revista Archai, 2019)
The Constitution of the Athenians is a short work about the politeia of Athens and the conditions by which Athenian democracy can last as constitutional regime which manages the life of the polis. This work represents both a philological and a historiographical problem, because, even if it was transmitted in the corpus of Xenophon’s work, it is considered to have been written by another author, known as Speudo-Xenophon or “Old Oligarch”. It is an oligarchic pamphlet which presents Athens as an upside down world, where the worst people rule and the best ones are as reduced to slavery by the ignorant multitude.